Analysis And Design Analysis And Design Of Decision Supporting Information System For Assessment Of Recruitment And Employees Management With Analytical Hierarchy Process (Ahp) Method In PT. Indo Porcelain - Tri Hartati; Rino Rino (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2018)
Managing human resources in the company is very important where human resources are needed for the progress of the company, in most companies, of course, can utilize all the human resources obtained in accordance with the need to contribute in accordance with the needs of the company to achieve its goals. PT. Indo Porcelain is engaged in manufacturing with ceramic dining table products, such as glassware, bowls and dishes. Problems faced by PT. Indo Porcelain is the absence of an integrated information system, so that the employee recruitment process requires time in making selection decisions for prospective employees while at the same time hampering the company's internal control. Based on the concept and design, it can be concluded that it has been built